2014
DOI: 10.1007/s13277-014-2444-5
|View full text |Cite
|
Sign up to set email alerts
|

Different mutational characteristics of TSG in cell lines and surgical specimens

Abstract: One of the most crucial concerns of cancer research pertains to the differences between the neoplastic cells in tumor specimens in vivo and their counterparts in cell lines. The huge amount of results deposited in cancer genetic databases allows to address this issue from a wider perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 11 , 14 One study has reported the tumorigenicity of cells from a primary gliosarcoma at early passage in serum condition, and some commercially available glioma cell lines are tumorigenic in serum condition, but these cell lines were criticized recently. 15 , 16 , 17 Another widely used method for enrichment of GSCs is cell sorting based on CD133 expression. 2 , 18 However, this is not a reliable method as some CD133-negative cells can also be tumorigenic, and some fresh and in vitro -expanded GBM specimens do not express CD133.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 14 One study has reported the tumorigenicity of cells from a primary gliosarcoma at early passage in serum condition, and some commercially available glioma cell lines are tumorigenic in serum condition, but these cell lines were criticized recently. 15 , 16 , 17 Another widely used method for enrichment of GSCs is cell sorting based on CD133 expression. 2 , 18 However, this is not a reliable method as some CD133-negative cells can also be tumorigenic, and some fresh and in vitro -expanded GBM specimens do not express CD133.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have previously described that there is a higher frequency of homozygous mutations in tumor suppressors as well as mutations resulting in lack of tumor suppressor proteins in cell lines when compared to surgical samples. Hence, there seems to be a complete loss of function of tumor suppressor genes in time [23]. On the other hand, mesenchymal GB subtype is suggested to be more prone to stabilization, even if patient was diagnosed with another GB subtype [16], what seems to be reasonable, as cells in monolayer conditions attach to the culture vessel and compete with normal stromal cells [24].…”
Section: Discussionmentioning
confidence: 99%